An improved quantitative assessment method on hazardous interference of power lines to the signal cable in high‐speed railway - Chang Liu; Shiwu Yang; Yong Cui; Shaotong Chu; Qihui Xiong (IET Electrical Systems in Transportation)
Abstract High‐speed railway (HSR) presents the characteristics of a heavy load, large traction current, and ballastless track‐bed. As the 'neural network' of the signalling system, the line‐side signal cable may threaten both human safety and control information transmission for an HSR operation when interfered with by a strong traction current. This study comprehensively investigates the electromagnetic interference (EMI) factors of the traction power supply system (TPSS) and the integrated earthing system (IES) to a signal cable and completes the electromagnetic coupling mechanism analysis of longitudinal electromotive force (LEF). Then, an improved theoretical calculation method is proposed for the multi‐conductor power line network of the HSR instead of the traditional look‐up table method. Regarding the essential influence of different earthing methods and cable laying conditions, the quantitative calculation of the LEF on the cable is evaluated. The validity of the theoretical method is verified through finite element simulation. Finally, the solutions to suppress the EMI are put forward for cable laying. This work provides an accurate quantitative basis for the implementation of the on‐site LEF test, is significant for the design of cable laying schemes in railway engineering, and is also beneficial to ensure the safe operation of HSR.